Determinants of factors that affect external debt in Malaysia / Akmal Asyraf Yahya - Yahya, Akmal Asyraf (2013)
The purpose of this study is to investigate the determinants contributing to the factors that affect external debt in Malaysia, covering the period of 1972-2012. Multiple Regression Analysis (MRA),graph analysis, Unit Root Test and Granger Causality Test are carried out to examine the various factors such as the dynamic effect of Gross Domestic Product, export and foreign direct investment were taken to determine their statistic relationship with the external debt in Malaysia. For this purpose, the researcher used secondary data, which is a data gather from World Bank. This Study will beneficial to the government and also to the company and individual in Malaysia. Summarizing the findings of this study, all factors has a significant result. Gross Domestic Product, export and foreign direct investment shows significantly influence toward External Debt in Malaysia. As conclusion, Gross Domestic Product, Foreign Direct Investment and Export are affecting external debt in Malaysia because the more income government got, it will be reduce the external debt